THE The Influence of Capital, Labor and Length of Business on Traders' Income in the Beringkit Animal Market Badung Regency - I M. Sudiyasa; I. B. N. Wiratmaja; Ngurah Wisnu Murthi; I. K. Djayastra (Social Science Academic, 2023)
he current development of the Indonesian economy can be measured by the development of trade centers. The existence of a trade center is one of the most obvious indicators of community economic activity in a region. In terms of economic interests, the increasing number of trade centers, both traditional and modern, encourages the creation of job opportunities for many people. Starting from the services of security forces, shopkeepers, delivery people, cleaning services, to transportation services. This means that the presence of a trade center participates in alleviating the problem of poverty. This research uses quantitative research methods and statistical analysis, especially analysis of numbers and statistical analysis with the aim of confirming previously established hypotheses. Multiple linear regression method, partial test and simultaneous F test. Based on the SPSS calculation results, results were obtained 1). The income of traders at the Beringkit animal market in Badung Regency is partly positively and significantly influenced by capital, labor, but not significantly by the length of business. 2) The income of traders at the Beringkit animal market in Badung Regency is also simultaneously influenced positively and significantly by capital, labor and length of businesshe current development of the Indonesian economy can be measured by the development of trade centers. The existence of a trade center is one of the most obvious indicators of community economic activity in a region. In terms of economic interests, the increasing number of trade centers, both traditional and modern, encourages the creation of job opportunities for many people. Starting from the services of security forces, shopkeepers, delivery people, cleaning services, to transportation services. This means that the presence of a trade center participates in alleviating the problem of poverty. This research uses quantitative research methods and statistical analysis, especially analysis of numbers and statistical analysis with the aim of confirming previously established hypotheses. Multiple linear regression method, partial test and simultaneous F test. Based on the SPSS calculation results, results were obtained 1). The income of traders at the Beringkit animal market in Badung Regency is partly positively and significantly influenced by capital, labor, but not significantly by the length of business. 2) The income of traders at the Beringkit animal market in Badung Regency is also simultaneously influenced positively and significantly by capital, labor and length of business